Three new species of Orchestina Simon, 1882 (Araneae, Oonopidae) from Xizang, China - Yang Zhou; Yanfeng Tong; Dongju Bian; Shuqiang Li (ZooKeys)
The genus Orchestina is recorded for the first time from Xizang, China. One known species and three new species are reported: Orchestina colubrina Liu, Henrard & Xu, 2019 (♂♀), Orchestina lini Tong & Li, sp. nov. (♂♀), Orchestina wuzu Tong & Li, sp. nov. (♂♀) and Orchestina yigong Tong & Li, sp. nov. (♂).